Beispiel Nr: 02
$\text{Gegeben:}\\\text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\\text{Mantelfläche} \qquad M \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Grundfläche} \qquad G \qquad [m^{2}] \\ \\ G = O-M\\ \textbf{Gegeben:} \\ O=4m^{2} \qquad M=6m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ G = O-M \\ M=6m^{2}\\ O=4m^{2}\\ G =4m^{2}-6m^{2}\\\ G=-2m^{2} \\\\\\ \tiny \begin{array}{|l|} \hline O=\\ \hline 4 m^2 \\ \hline 400 dm^2 \\ \hline 4\cdot 10^{4} cm^2 \\ \hline 4\cdot 10^{6} mm^2 \\ \hline 0,04 a \\ \hline 0,0004 ha \\ \hline 4\cdot 10^{-6} km^2 \\ \hline \end{array} \tiny \begin{array}{|l|} \hline M=\\ \hline 6 m^2 \\ \hline 600 dm^2 \\ \hline 6\cdot 10^{4} cm^2 \\ \hline 6\cdot 10^{6} mm^2 \\ \hline 0,06 a \\ \hline 0,0006 ha \\ \hline 6\cdot 10^{-6} km^2 \\ \hline \end{array} \tiny \begin{array}{|l|} \hline G=\\ \hline -2 m^2 \\ \hline -200 dm^2 \\ \hline -2\cdot 10^{4} cm^2 \\ \hline -2\cdot 10^{6} mm^2 \\ \hline -0,02 a \\ \hline -0,0002 ha \\ \hline -2\cdot 10^{-6} km^2 \\ \hline \end{array}$